ANALISIS AKIBAT HUKUM TERHADAP PELANGGARAN HAK CIPTA ATAS PEMBAJAKAN FILM DI BIOSKOP MELALUI APLIKASI TELEGRAM - NIM. A1011191206, MAWAR CANTIKA DISTA (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract Copyright is a right granted to the creator of intellectual work to protect their economic and moral interests in their work. Creators can protect their work from illegal use by irresponsible individuals, one of which is the protection of Films or Cinematographic Works, regulated in Chapter V Article 40 paragraph (1) of Law Number 28 of 2014 concerning Copyrights. However, the rapid technological development has a negative impact on copyright infringement, such as film piracy in cinemas conducted through social media, namely the Telegram Application. The problem of this research is: